The effect of birth weight and time of day on the thermal response of newborn water buffalo calves - Napolitano, Fabio; Bragaglio, Andrea; Braghieri, Ada; El-Aziz, Ayman H. Abd; Titto, Cristiane Gonçalves; Villanueva-García, Dina; Mora-Medina, Patricia; Pereira, Alfredo M. F.; Hernández-Avalos, Ismael; José-Pérez, Nancy; Casas-Alvarado, Alejandro; Lezama-García, Karina; et al. (Frontiers in Veterinary Science, 2023)
During the first days of life, water buffalo calves, especially those with low birth weight, are susceptible to hypothermic mortality due to scarce energy reserves provided by fats. This means that monitoring the thermal state of newborns is essential. The objectives of the present study were to apply infrared thermography (IRT) in 109 buffalo calves to detect differences in the surface temperatures of six thermal windows –lacrimal gland, lacrimal caruncle, periocular region, nostrils, ear canal, pelvic limbs– and determine their association to birth weight during the first six days of life. The calves were divided into four categories according to their weight (Q1, 37.8-41.25 kg; Q2, 41.3-46.3 kg; Q3, 46.4-56.3 kg; Q4, 56.4-60.3 kg). The thermographic images were recorded in the morning and afternoon. Results showed that the animals in Q4 registered the highest temperatures in all the thermal windows, and that these were higher in the afternoon (p<0.0001). When considering the thermal windows, those located in the facial region recorded the highest temperatures; in contrast, the temperatures at the pelvic limbs remained below the average values of the other windows (33.41°C and 33.76 °C in the morning and afternoon, respectively). According to these results, the birth weight of water buffaloes is a factor that alters their thermoregulation during the first days of life, a condition that can be partially compensated by colostrum intake to promote development of an efficient thermoregulatory mechanism in water buffalo calves.